Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3109/14767058.2015.1024649
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrical and neonatal outcomes of triplet births – spontaneous versus assisted reproductive technology conception

Abstract: Rates of preterm birth and related complications remain high in triplet gestation. However, obstetrical and neonatal outcomes were similar for triplets conceived spontaneously versus via ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
14
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 27 publications
7
14
4
Order By: Relevance
“…Similar to our study, there were no differences in maternal or neonatal complications studied between both groups. 4 However, in both Fennessy et al 4 and Morency et al, 7 no confounders were adjusted; our study accounted for this to assess any true differences in outcomes from triplets conceived by ART. Of note, triplets conceived by ART were more likely to have trichorionic triamniotic (TCTA) placentation; TCTA triplets had lower mortality rates than other triplet combinations.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Similar to our study, there were no differences in maternal or neonatal complications studied between both groups. 4 However, in both Fennessy et al 4 and Morency et al, 7 no confounders were adjusted; our study accounted for this to assess any true differences in outcomes from triplets conceived by ART. Of note, triplets conceived by ART were more likely to have trichorionic triamniotic (TCTA) placentation; TCTA triplets had lower mortality rates than other triplet combinations.…”
Section: Discussionmentioning
confidence: 94%
“…Similar to our study, neonatal complications were studied as a secondary outcome and no significant differences were found between both groups. 7 Differences in GA at birth can likely be attributed to ART patients being more associated with a higher socioeconomic status and education level leading to earlier and better access to prenatal care and a healthier lifestyle. 21 In our multivariate logistic regression, ethnicity and GA at delivery were the factors that made the largest difference to the ORs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The degree of GCT discordance was greatest in pregnancies with triplet fetuses, whilst it was still significantly altered in those with twins ( 54 ). An independent examination of pregnancies with triplet fetuses indicated that 10% were affected by GDM ( 55 ).…”
Section: Gdm and Pe: The Issue Of Placental Massmentioning
confidence: 99%